Kruīza kuģu tūrisma ietekme uz ekonomiku un vidi ziemeļvalstīs - Peltola, Elliot Johan August (Latvijas Universitāte, 2025)
Šajā bakalaura darbā tiek pētīts kruīzu tūrisms Ziemeļvalstīs, izvērtējot tā ekonomisko un vides ietekmi. Darba mērķis ir analizēt, vai kruīzu tūrisma ekonomiskā ietekme atsver tā radīto vides slodzi, lai sniegtu ieteikumus politikas veidotājiem un nozares speciālistiem ilgtspējīgas attīstības nodrošināšanai. Izmantojot Helsinku un Stokholmas gadījumu izpēti, darbs aplūko galvenās tendences, ārējos efektus un reģionālās atšķirības. Rezultāti atklāj gan ieguvumus, gan izaicinājumus kruīzu tūrismā un sniedz praktiskus ieteikumus nozares ilgtspējīgai attīstībai.

This bachelors thesis researches cruise ship tourism in the Nordic countries by evaluating its economic and environmental impact. The goal of this bachelor’s thesis is to analyse whether the economic impacts outweigh the environmental impacts of cruise ship tourism in the Nordic countries to provide recommendations for policymakers and industry specialists to ensure the long-term sustainability of the industry. Using case studies of Helsinki and Stockholm, the thesis examines key trends, externalities, and regional differences. The results highlight both the benefits and the challenges of cruise tourism and offer practical suggestions for sustainable development in the sector.
The Economic and Environmental Impact of Cruise Ship Tourism in the Nordic Countries
Keywords: Ekonomika un uzņēmējdarbība; cruise tourism; economic impact; environmental sustainability; Nordic countries; sustainable development